THE PREFERENCE OF FOREIGN-BASED (MIGRANT) PLAYERS OVER HOME-BASED PLAYERS IN THE SUPER EAGLES OF NIGERIA: A COLORATION OF ‘COLONIAL MENTALITY’ - JOSEPH OKECHUKWU NWOKE (International Studies Journal)
Nigeriais blessed with talented footballers. There abound Nigerian players in the Nigeria Professional Football League and foreign leagues. The Nigeria Football Federation(NFF) is in charge of running football in Nigeria as it superintends over the Nigerian national football teams and recruit coaches. Both home-based and foreign-based players were always invited to the camp of the Super Eagles when there was a competition. However,when it was time for the final list to be drawn there might not be any home-based players in the list or there might be an insignificant number that might end up not playing in such competition.There has been a lot of talk on the preference of foreign-based players over home-based players in the Super Eagles team.Hence, this study analyses the rate of selection in terms of percentage of home-based and foreign-based players in the Super Eagles team by some selected foreign and Nigerian coaches.The Hamitic hypothesis of Seligman is applied to show the nexus to the preference for foreign-based players.This study makes use of   primary and tertiary sources of data.Findings reveal that not only foreign coaches solely relied on foreign-based players, as some Nigerian coaches were equally masterminds of the unpatriotic act. Also, home-based players can be instrumental to performance of the team as was displayed in the 1990 and 2013 African Cup of Nations.This study recommends that a law should be passed forcing the coach to include at least four home-based players on the field of play whenever the team is in action.